2014
DOI: 10.1080/00207543.2014.937012
|View full text |Cite
|
Sign up to set email alerts
|

Balancing mixed-model assembly lines with adjacent task duplication

Abstract: When a mixed-model assembly line (MAL) is balanced, it is generally assumed that the variants of a task over different models should be assigned to an identical station. In this study, this restriction is relaxed and the variants of a task over different models can be duplicated on two adjacent stations (referred to as adjacent task duplication) to improve the MAL's efficiency. The adjacent task duplication incurs few additional training and tool duplication costs as each task is duplicated on at most two stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…They proposed 28 workload smoothing criteria and investigated them using branch and bound algorithm and found that they play a vital role in planning and executing the mixed-model assembly line balancing problem. Yang et al [14] considered the mixed-model assembly line balancing problem in which the variants of a task to different models should be assigned to an identical workstation is relaxed. That is variants of a task over different models can be duplicated on two adjacent workstations to improve the balancing efficiency.…”
Section: Branch and Bound Methodsmentioning
confidence: 99%
“…They proposed 28 workload smoothing criteria and investigated them using branch and bound algorithm and found that they play a vital role in planning and executing the mixed-model assembly line balancing problem. Yang et al [14] considered the mixed-model assembly line balancing problem in which the variants of a task to different models should be assigned to an identical workstation is relaxed. That is variants of a task over different models can be duplicated on two adjacent workstations to improve the balancing efficiency.…”
Section: Branch and Bound Methodsmentioning
confidence: 99%
“…The use of cross-trained workers is recognized as a solution to problems related to efficiency and flexibility in ALBP (see Hopp et al (2004) and Yang et al (2014)). However, across industries, cross-trained workers are usually limited in number and more expensive than single-skilled workers, because of higher wages or because of the training they had.…”
Section: Proceedings Of the 20th World Congressmentioning
confidence: 99%